Principal Management in Improving the Quality of Education in Madrasahs - Mia Rahmadina (Sufiya Journal of Islamic Studies, 2024)
This study aims to examine the management of madrasah principals in improving the quality of education at MTs T Darul Huda Medan Marelan. The main focus of this research is to find out how the planning, implementation, organization, and supervision carried out by the madrasah principal in improving the quality of education. The method used in this research is qualitative with a case study approach, with data collection techniques through interviews with principals and teachers. The results showed that the management applied by the madrasah principal plays a role in improving the quality of education, through steps that include careful planning, effective organization of resources, and strict supervision of the implementation of educational activities. The principal also provides the motivation and guidance needed to support teachers' professionalism in carrying out their duties.